Pengaruh Green Corporate Governance, Umur Perusahaan, dan Financial Distress Terhadap Kualitas Audit - Yuliyani Yuliyani; Kurnia Indah Sumunar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to analyze the effect of green corporate governance on audit quality, to analyze the effect of firm age on audit quality, and to analyze the effect of financial pressure on audit quality. The population in this study is the transportation sub-sector listed on the Indonesia Stock Exchange while the sample of this research company is 18 manufactures that meet the sample criteria during the study period. The sampling technique in this study used the probability sampling method. Data analysis used is logistic regression analysis. The results showed that green corporate governance has no significant negative effect on audit quality, firm age has a significant positive effect on audit quality, financial distress has a significant positive effect on audit quality.